10-year Portuguese football strategic plan: sustainable growth - Sousa, Nuno Da Cunha Monteiro (2022)
This individual contribution is a supplement to the FPF's group analysis of the main pillars within the strategy to be defined for the next ten years in Portuguese football. Within this paper, FPF goals as a not-for-profit institution are analysed. Moreover, how an income shared agreement works as a potential model for monetizing and how a scholarship for female university football athletes can benefit both students and the sponsor is analysed The overall financial health of the federation is analysed and understood as healthy and capable of promoting the scholarship program